A genre analysis of formula milk pamphlets and sample boxes / Delicia Ng Ly-Ann - Ng, Delicia Ly-Ann (2015)
This is a study on the move structure of formula milk product pamphlets and sample boxes that are chosen by Malaysian parents for their toddlers. The framework used to analyse the samples in this study is the nine-move structure for advertisements introduced by Kathpalia (1992). The main outcome of this study is to find out the communicative purpose of formula milk pamphlets and sample boxes and the rhetorical structure that is used to create these samples. The study finds the information desired by parents, in order to make an informed decision to help advertisers decide how to best use the limited space available. Those moves that have a frequency of 75% or above are prominent moves. The results of the findings show that the communicative purpose of the formula milk pamphlets and sample boxes are to inform and persuade potential customers to buy the product. The prominent moves of this study is Appraising the Product, Identifying the Company, Urging Action, Attracting Action, Justifying the Product, and giving Related Information that helped realize the communicative purposes. Interpersonal metadiscourse occurred in 78% of the pamphlets and sample boxes to engage the reader and to realize the different moves. The findings also show that the top three information that parents need in order to make an informed decision on the formula milk for their child is the ingredients used to make the product, where it is produced, and what needs of their child it meets. It is hoped that from this research findings, a better understanding of the structure of formula milk advertisements can be achieved.